2017
DOI: 10.1016/j.heliyon.2017.e00416
|View full text |Cite
|
Sign up to set email alerts
|

Placental extract ameliorates non-alcoholic steatohepatitis (NASH) by exerting protective effects on endothelial cells

Abstract: Non-alcoholic steatohepatitis (NASH) is a severe form of fatty liver disease that is defined by the presence of inflammation and fibrosis, ultimately leading to cirrhosis and hepatocellular carcinoma. Treatment with human placental extract (HPE) reportedly ameliorates the hepatic injury. We evaluated the effect of HPE treatment in a mouse model of NASH. In the methione- and choline-deficient (MCD) diet-induced liver injury model, fibrosis started from regions adjacent to the sinusoids. We administered the MCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
1
28
0
3
Order By: Relevance
“…In an earlier study, we generated a NASH model by feeding a methionine-and choline-deficient (MCD) diet with high-salt loading (8% NaCl in the drinking water) to mice deficient in the vasoprotective molecule RAMP2 for 5 weeks (36). In this model, fibrosis was observed in regions adjacent to the sinusoids in control mice but the fibrosis was less pronounced in hPE-treated mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier study, we generated a NASH model by feeding a methionine-and choline-deficient (MCD) diet with high-salt loading (8% NaCl in the drinking water) to mice deficient in the vasoprotective molecule RAMP2 for 5 weeks (36). In this model, fibrosis was observed in regions adjacent to the sinusoids in control mice but the fibrosis was less pronounced in hPE-treated mice.…”
Section: Methodsmentioning
confidence: 99%
“…6A). Regarding the molecular weight distributions of these In an earlier study, to accelerate the damage of sinusoidal endothelial cells, we modified the MCD model by combining it with high-salt loading and used mice deficient in Receptor activity modifying protein 2 (RAMP2), a molecule involved in mediating endothelial viability (36). Using that model, we showed that hPE treatment ameliorated NASH pathology by preventing the damage of sinusoidal endothelial cells.…”
Section: Effect Of Hpe Fractions On Suppressing Hepatic Stellate Ri-tmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental extract can be simply obtained by hydrolysis of the placenta via both hydrochloric acid and enzymatic digestion, and it has been reported to have many biological activities in vitro and in vivo (Bak et al, 2018(Bak et al, , 2019Ito, Yamada, Matsumoto, & Imamura, 2018;Yamauchi et al, 2017;Yoshimoto et al, 2018). There are now several placental extract products available, and these have been used as drugs or in health care.…”
Section: Introductionmentioning
confidence: 99%
“…Normal diet (N), high-fat/high-sucrose diet (C), high-fat/high-sucrose diet containing carotene at a low dose (0.001% by mass) (LC), or high-fat/high-sucrose diet containing carotene at a high dose (0.004% by mass) (HC in mice was closely associated with reduced MMP-9 expression (Yamauchi et al, 2017). However, other proinflammatory cytokines may be related to liver fibrosis.…”
Section: Edmentioning
confidence: 99%